Montage experimentation as pedagogical strategy: a practice-led and artistic research study of student films in Bandung, Indonesia - Pauhrizi, Erik Muhammad; Supiarza, Hery; Warsana, Dedi; Ernawan, Erika; Alfathadiningrat, Danendra (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2025)
Film education in Indonesia, often prioritizing industry goals, forcing students to adapt to industry targets and serve the economic gains over artistic achievement. As Indonesian Film and Television Study Program Association (PROSFISI) stated, this industry-oriented view correlates to students who merely consume foreign film entertainment, causing them to become less active, creative, and connected to Indonesian culture and identity. An approach like this breeds a lack of critical thinking and a limited artistic imagination with montage as a contextual device. The purpose of this study is to demonstrate that recreate montage in filmmaking education in Indonesia is an opportunity to renew freedom, cultural address, and critique. Through Practice-Led and Artistic Research, the research was conducted in the Film Study Program Bandung, analyzed the application of montage theories by Eisenstein, Pudovkin and Vertov, on student films. Findings suggest that narrative and symbolic montage facilitated deeper meaning around local topics and more straightforward and emotionally resonant narratives. Through a consideration of social-cultural issues the study shows the power of the montage as both an artistic and research tool. This study argues that the curriculum should approach film as a tool that promotes experimentation integrating montage and local culture to deepen student” understanding of film beyond its commodified nature.